2020
DOI: 10.3390/ijerph17062013
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Vertebrobasilar Calcification in Patients with Ischemic Stroke Is a Predictor of Recurrent Stroke, Vascular Disease, and Death: A Case-Control Study

Abstract: Intracranial artery calcification can be detected on nonenhanced brain computer tomography (NECT) and is a predictor of early vascular events. Here, we assessed the impact of vertebrobasilar artery calcification (VBC) on the long-term risk for recurrent stroke and vascular events. We performed a case-control trial of all consecutive stroke patients admitted to the University Hospital of Maribor, Slovenia over a period of 14 months. VBC was defined as presence of a hyperdense area within vertebrobasilar arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(40 reference statements)
0
13
0
Order By: Relevance
“… 6 Vertebrobasilar calcification in patients with ischemic stroke is a valid predictor for stroke recurrence and acute vascular disease. 7 Coronary artery calcification in patients with atrial fibrillation has increased the independent risk of stroke, 3 but carotid calcification is not associated with incident stroke. 8 …”
mentioning
confidence: 99%
“… 6 Vertebrobasilar calcification in patients with ischemic stroke is a valid predictor for stroke recurrence and acute vascular disease. 7 Coronary artery calcification in patients with atrial fibrillation has increased the independent risk of stroke, 3 but carotid calcification is not associated with incident stroke. 8 …”
mentioning
confidence: 99%
“…Previous studies revealed the key role of serum calcium in the promotion of vascular calcification, which is a complex process including the promotion of osteogenic/chondrogenic differentiation, vesicle release, cell apoptosis, loss of inhibitors, and extracellular matrix degradation ( 31 , 32 ), leading to atherosclerosis. Thus, elevated serum calcium levels may accelerate the process of atherosclerosis, cardio-cerebrovascular calcification, and plaque rupture which has been associated with poor clinical outcomes ( 33 35 ). In addition, calcium ion is a crucial intracellular messenger, and plays a key role in neuronal damage and cell death ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with TIA, a higher calcium volume was associated with a higher risk of recurrent TIA or AIS ( Kong et al, 2019 ). In addition, two studies found that in patients with AIS, the presence of VBA calcification is also associated with long-term risk of recurrent stroke ( Gökçal et al, 2018 )and mortality ( Magdič et al, 2020 ). As for stroke subtypes, IAC was associated with a higher risk of recurrence only in patients with index small-vessel occlusive stroke ( Wu et al, 2020 ), suggesting that IAC might serve as a valuable predictor of recurrence in this subtype of stroke.…”
Section: Intracranial Artery Calcificationmentioning
confidence: 99%